Cardiopulmonary Capacity in Children During Exercise Testing: The Differences Between Treadmill and Upright and Supine Cycle Ergometry - Forbregd, Tonje Reitan; Aloyseus, Michelle Arthy; Berg, Ansgar; Greve, Gottfried (Frontiers in Physiology, 2019)
1.1 Background/hypothesis Cardiopulmonary exercise testing (CPET) is used in the assessment of function and prognosis of cardiopulmonary health in children with cardiac- and pulmonary diseases. New techniques, such as echocardiography, cardiac MRi, and PET-scan, can be performed simultaneously with exercise testing. Thus, it is desirable to have a broader knowledge about the children’s normal cardiopulmonary function in different body postures and exercise modalities. The aim of the present study was to investigate the effect of different body positions, when performing a CPET, on cardiopulmonary function. 1.2 Materials and methods Thirty-one children in three different age groups (9-, 12- and 15-year-olds) did four different CPETs. Parents gave informed written consents. The CPET’s consisted of a treadmill test with a modified Bruce protocol and three bicycle tests with different body postures. For the bicycle tests, we used a 20-watt ramp protocol with a pedal frequency of 60±5 rotations per minute. During the tests, we performed continuous ECG monitoring and breath-by-breath V̇O2 measurements. Echocardiography was performed prior to the tests and Doppler measurements of the blood velocity in the ascending aorta was measured before and every minute during the test. Prior to every test the participants performed pulmonary function tests with maximum voluntary ventilation test. 1.3 Results There was a significantly (p<0.05) lower peakV̇O2 in all bicycle tests compared with the treadmill test. However, there was no significant difference between the bicycle tests regarding relative peakV̇O2. A difference in absolute peakV̇O2 between the upright bicycle and the supine bicycle was found. There were no differences in peak stroke volume or cardiac output between the bicycle modalities when calculated from aortic blood flow. Peak heart rate did decrease from both treadmill to upright bicycle and from upright bicycle to the supine test. 1.4 Conclusion We did not find any differences in relative peakV̇O2 or cardiac output between the upright bicycle test and supine bicycle tests. Heart rate and absolute peakV̇O2 show differences between the upright bicycle and supine bicycle.